Genki ice cream / Muhammad Mat Zaib ...[et al.] - Mat Zaib, Muhammad; Md Alias, Muhammad Firdaus; Danial, Muhammad Hafidz; Hamle, Muhammad Haziq (2023)
GENKI Ice Cream Sdn. Bhd is a manufacturer company that make a healthy concept product, which is a product called “Fruit Ice Cream” that is healthy and nutritious for consumers, which is suitable for person who trying to be on track of their calorie and maintaining diet by consuming a healthy dessert which is less worry to the consumer. Our primary strategy and aim is to provide a product that is affordable and healthy to consumers. Our objective in our company is to be successful and become expandable business in future, and also trying to achieve a huge networking in future. We always looking forward to our consumer satisfaction towards our products. Since our company is listed as a new company in the market, so there will be many aspects that we need to consider in order to make sure that our company can compete with other manufacturing company and fulfill the consumers need as there are many involvements in business industry, especially those who involve in food and beverages industry. The product that we offered is ice cream, which is our main product manufacturing and might be add another product in future, depending on the business stability. Nowadays, there are many problem that the consumer faced, especially when they complaint about some ice cream use artificial stabilizers, which harm to human body. We see this as research and development product on how to make a product that is healthy and less harm towards our consumer and also flavourful. Our company is run by four main manager which is General Manager, Marketing Manager, Operation Manager and Financial Manager. All of manager is play a vital role in this business and will make sure that this company will be successful and gaining achievements more in the future. From observation, the company are targeting a big scope of customer by achieving a business-to-business deal which makes our product supply larger and will grow in future. Our potential in the market is by targeting the every people that need a good diet and healthy lifestyle. The company also target as many of consumer buy our products and enjoy the products with good feedback. Furthermore, our manufacturing company is located at a very strategic location, which is easy for dealing